Evaluation of Organic and Vermicompost-based Trichoderma harzianum Formulation for Seedling Disease Management and Yield Enhancement in Chickpea (Cicer arietinum L.) - Faruk, Md. Iqbal; Akhter, MS; Islam, R; Rahman, M; Alam, MM (Archives of Case Reports, 2025)
Seedling diseases caused by soil-borne pathogens pose a significant threat to chickpea (Cicer arietinum L.) production, often resulting in poor plant stand, reduced growth, and substantial yield losses. Eco-friendly and sustainable disease management strategies are therefore essential to minimize chemical inputs while enhancing soil and plant health. In this study, organic composts and vermicompost were screened as carrier materials for the formulation of Trichoderma harzianum, an effective biocontrol agent, to evaluate their efficacy in managing seedling diseases caused by soil-borne pathogens, Sclerotium rolfsii and Fusarium oxysporum f. sp. ciceri, and promoting growth and yield of chickpea. The experiments were conducted in the fields of the Plant Pathology Division, Bangladesh Agricultural Research Institute, Gazipur, during 2018-19, 2019-20, and 2020-21 cropping years to evaluate the antagonistic potential of organic composts and vermicompost-based T. harzianum formulations designated as Tricho-organic-compost and Tricho-vermi-compost on seedling emergence, disease incidence, plant growth, and grain yield of chickpea. Seed treatment with fungicide Provax 200 WP was also tested. Results revealed that T. harzianum enriched organic composts and vermicompost, viz. Tricho-organic-compost and Tricho-vermi-compost soil, seed treatment by Provax 200 WP, and soil amendment with organic-compost and vermi-compost were effective in reducing seedling mortality and increasing plant growth and yield of chickpea compared to the control. Among the treatments, T. harzianum enriched organic composts and vermicompost, viz. Tricho-organic-compost and Tricho-vermi-compost exhibited superior for significant reduction in seedling mortality, and enhancement in plant growth parameters, and increased yield of chickpea compared to untreated control and other treatments. The study underscores the potential of compost-based T. harzianum formulations as sustainable tools for integrated management of chickpea seedling diseases while enhancing crop productivity. Seed treatment with the chemical fungicide Provax 200 WP was also a better treatment for managing seedling disease and increasing plant growth and yield of chickpea.